Ba Zee Gala Njinga Mi NDA Du Toko Ta Ba Yati Gi Kuro Mi Yo E We Kitabu Mi NDA Mbe Ji Nji (Ta NDA Ngu I Gbi). A Co Giti Kpolokpolo NDA I: Kitabu 2 Do Ti 3 - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon R.; Gupta, Arnab (2022)
N’dogo edition of: Vernooy, R.; Bessette, G.; Sthapit, B.; Gupta, A. (2018) How to develop and manage your own community seed bank: Farmers’ handbook. Technical issues: Booklet 2 of 3. This handbook is a companion to Vernooy, R., Sthapit, B. and Bessette, G. (2020). Community seed banks: concept and practice. Facilitator handbook (updated version). Bioversity International, Rome, Italy (https://hdl.handle.net/10568/81286). The three booklets making up this handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Booklet 1 can be found here: https://hdl.handle.net/10568/118297. Booklet 3 can be found here https://hdl.handle.net/10568/118313. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Translation and adaptation to the local language is encouraged. If you would like to receive a hard copy of the booklets or give feedback or suggestions for improvement, please contact r.vernooy@cgiar.org.